The Impact of Artificial Intelligence (AI) on Financial Management - Hidayat, Muhammad; Defitri, Siska Yulia; Hilman, Haim (Penelitian dan Pengembangan Ilmu, 2024)
This study examines the impact of artificial intelligence (AI) on financial control, exploring the implementation of AI technology in financial selection-making strategies, predictive analysis and hazard manipulation. the use of a systematic literature examine approach, this studies covers the substantial modifications delivered via using AI in improving operational overall performance, presenting deep insights for financial preference making, and improving customer revel in in the banking area.. Even though it provides great benefits, this research also highlights ethical challenges, data security, adoption risks, as well as the need for policy and regulatory adjustments to the development of AI technology in the context of financial management. It is hoped that the results of this research can provide guidance for companies and policy makers in facing revolutionary changes in financial management in the digital era.